2014
DOI: 10.15252/embj.201489456
|View full text |Cite
|
Sign up to set email alerts
|

Dusp5 negatively regulates IL ‐33‐mediated eosinophil survival and function

Abstract: Mitogen-activated protein kinase (MAPK) activation controls diverse cellular functions including cellular survival, proliferation, and apoptosis. Tuning of MAPK activation is counter-regulated by a family of dual-specificity phosphatases (DUSPs). IL-33 is a recently described cytokine that initiates Th2 immune responses through binding to a heterodimeric IL-33Ra (ST2L)/IL-1a accessory protein (IL-1RAcP) receptor that coordinates activation of ERK and NF-jB pathways. We demonstrate here that DUSP5 is expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 69 publications
(78 reference statements)
3
48
0
Order By: Relevance
“…It is likely that the most effective extension of our current work will be to determine the effects of Dusp5 loss in human cancer cell lines with different oncogenic backgrounds combined with the use of murine models that allow tissue-specific conditional expression of BRAF V600E and Dusp5 deletion to further define the in vivo significance of our results. Finally, DUSP5 has recently been shown to regulate ERK-dependent gene expression and survival in eosinophils, and to modulate responses to helminth infection in mice (49). The latter results indicate that the relevance of our work may extend beyond the regulation of oncogenic signaling to other diseases in which abnormal ERK activity has been implicated.…”
Section: Discussionmentioning
confidence: 58%
“…It is likely that the most effective extension of our current work will be to determine the effects of Dusp5 loss in human cancer cell lines with different oncogenic backgrounds combined with the use of murine models that allow tissue-specific conditional expression of BRAF V600E and Dusp5 deletion to further define the in vivo significance of our results. Finally, DUSP5 has recently been shown to regulate ERK-dependent gene expression and survival in eosinophils, and to modulate responses to helminth infection in mice (49). The latter results indicate that the relevance of our work may extend beyond the regulation of oncogenic signaling to other diseases in which abnormal ERK activity has been implicated.…”
Section: Discussionmentioning
confidence: 58%
“…The MAPK/ERK1/2 pathway can serve as an important cellular function, including proliferation. DUSP5 serves as the key regulator and repressor of this pathway [23]. The mechanisms that regulate DUSP5 expression during cardiac fibroblast activation, however, remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that eosinophils are important immune cells in the defense against A. suum invasive larvae [23]. Other experimental models confirmed the protective role of eosinophils against multiple helminths, including Strongyloides stercoralis [24], N. brasiliensis [25], and Heligmosomoides polygyrus [26]. Nevertheless, during T. canis and T. spiralis infection, eosinophils do not seem to have such a protective role.…”
Section: Immune Activation By Helminthsmentioning
confidence: 99%